Implementation of the Ottawa Hospital Pain Clinic stepped care program: A preliminary report. Issue 1 (1st January 2020) - Bell, Louise; Cornish, Peter; Gauthier, Renée; Kargus, Cristin; Rash, Joshua; Robbins, Rose; Ward, Susan; Poulin, Patricia A.
ABSTRACT: Background: Access to multidisciplinary pain management treatment in Canada is limited, with wait times up to 4 years. Stepped care approaches to mental health treatment have led to substantial reduction and elimination of wait times and may be applicable to chronic pain settings. There is no unifying framework for stepped care chronic pain programs. A systematic review of the efficacy of stepped care in chronic pain management conducted by the Canadian Agency for Drugs and Technologies reported varied results that may be due to heterogeneous stepped care models across facilities. Aim: We propose a unifying framework for multidisciplinary stepped care chronic pain programs and present its application at The Ottawa Hospital Pain Clinic. The Ottawa Hospital stepped care framework is an eight-tiered approach that allows patients the opportunity to decide collaboratively with a health care professional which treatment program will best suit their needs for the management of chronic pain. As levels of stepped care increase, the time and resource commitment to each step will also increase. Treatment is stepped up or down, depending on patient needs. Method: This is a descriptive case study. Results: Implementing the interprofessional model of care with the stepped care program has eliminated wait times for access to The Ottawa Hospital Pain Clinic Interprofessional Chronic Pain Management Program and has improved communication between professions of the interprofessional team, resulting in better care for patients. Conclusion: More research is needed to further develop and evaluate the clinical efficacy of stepped care to manage chronic pain.